Real-Time Underground Plastic Pipeline Water Leakage Detection and Monitoring System - Muhammad Haziq Hakim Rosman; Rozaimi Ghazali; Gowdie Palmer Derai; Hazriq Izzuan Jaafar; Chong Chee Soon; Dirman Hanafi; Zulfatman Has (International Journal of Robotics and Control Systems, 2022)
The leaking of the water pipeline increasingly influences the quality of life and threatens the water supplier in developing countries. Proper method is required to effectively detecting the source for replacement to reduce the loses. Therefore, a water leakage detection with monitoring system is developed to detecting the precise leaking location of a buried plastic pipeline. The real-time pressure data obtained from the pressurized pipeline are transferred to the monitoring system with GUI (graphical User Interface), developed using LabVIEW software. In the experimental execution, a leaking pipeline is designed. Then, few pressure sensors are installed on the pipeline as a primary segment for the detection process. To prevent a false non-leak alarm and malfunction of the pressure sensors, the pressure threshold value and malfunction alarm is set using LabVIEW. Cross-correlation method is implemented that increase the accuracy of the leaking distance estimation. The processing and control unit in this article are manipulated using LabVIEW software and NI myRIO-1900 respectively.